2017
DOI: 10.1038/nm.4453
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinating enzyme TNFAIP3 mediates inactivation of hepatic ASK1 and ameliorates nonalcoholic steatohepatitis

Abstract: Activation of apoptosis signal-regulating kinase 1 (ASK1) in hepatocytes is a key process in the progression of nonalcoholic steatohepatitis (NASH) and a promising target for treatment of the condition. However, the mechanism underlying ASK1 activation is still unclear, and thus the endogenous regulators of this kinase remain open to be exploited as potential therapeutic targets. In screening for proteins that interact with ASK1 in the context of NASH, we identified the deubiquitinase tumor necrosis factor alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
123
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 158 publications
(137 citation statements)
references
References 70 publications
5
123
1
Order By: Relevance
“…Ubiquitination is a vital mechanism that precisely modulates ASK1 activity, in which E3 ubiquitin ligases play a critical role in determining the ubiquitin linkage types of ASK1, thus modulating ASK1 activation or degradation . Our previous serial studies have shown that several ASK1 ubiquitination types involved in the pathogenesis of NASH had been identified, including Lys11‐, Lys29‐, Lys48‐, and Lys63‐linked ubiquitination . However, in this study, we identified a previously unknown ubiquitination types (Lys6‐linked) for ASK1.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Ubiquitination is a vital mechanism that precisely modulates ASK1 activity, in which E3 ubiquitin ligases play a critical role in determining the ubiquitin linkage types of ASK1, thus modulating ASK1 activation or degradation . Our previous serial studies have shown that several ASK1 ubiquitination types involved in the pathogenesis of NASH had been identified, including Lys11‐, Lys29‐, Lys48‐, and Lys63‐linked ubiquitination . However, in this study, we identified a previously unknown ubiquitination types (Lys6‐linked) for ASK1.…”
Section: Discussionmentioning
confidence: 56%
“…Accumulating evidence has widely demonstrated that apoptosis signal‐regulating kinase 1 (ASK1) is a potent driver of the inflammatory and fibrogenic responses by activating the downstream c‐Jun N‐terminal kinase (JNK)1/2‐mitogen‐activated protein kinase 14(p38) signaling cascade during NASH development . Moreover, inhibition of ASK1 is sufficient to mitigate onset and progression of NASH, making ASK1 a promising therapeutic target in NASH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Then, this complex phosphorylates and activates p38 and JNK, resulting in increase of hepatocyte injury via the BAX-caspase pathway, impairment of hepatic insulin resistance via Ser307 phosphorylation of insulin receptor substrate, increase of hepatic inflammation via pro-inflammatory cytokine/chemokine production, and increase of hepatic fibrosis via collagen production (39, 40). Recent emerging evidence suggests that several ASK1-interacting proteins such as Dickkopf-3 (DKK3), CASP8 and FADD-like apoptosis regulator (CFLAR, known as cFlip), and TNFα-induced protein 3 (TNFAIP3, known as A20) represent attractive therapeutic targets for the prevention and treatment of NAFLD/NASH (4143). Further understanding of molecular mechanisms underlying the regulation of ASK1 activity will provide opportunities to identify novel therapeutic targets and to develop promising therapeutic compounds for treatment of NAFLD/NASH.…”
Section: “Multiple-parallel Hit” Pathogenesis Of Nashmentioning
confidence: 99%
“…During metabolic stress, such as an excess of fatty acids, aberrant activation of ASK1 can lead to phosphorylation of p38 and the c‐Jun N‐terminal kinase (JNK) mitogen‐activated protein kinase (MAPK) pathway, which in turn triggers inflammatory and lipotoxic signaling that fuel the pathophysiology of nonalcoholic fatty liver disease (NAFLD)/NASH. Diverse posttranslational modifications determine the active state of ASK1, among which polyubiquitination is critical for subsequent ASK1 phosphorylation and activation . In addition to Lys48‐linked ubiquitination that mediates the degradation of ASK1, our previous study revealed other types of ubiquitination (Lys63‐, Lys29‐, and Lys11‐linked ubiquitination) that do not accompany protein degradation also regulate ASK1 activity in NASH .…”
mentioning
confidence: 90%